Leading virtual project teams : adapting leadership theories and communications techniques to 21st century organizations - Lee, Margaret R. (Boca Raton, Florida : Auerbach Publications, 2014)
In a 1945 speech, Winston Churchill stated, "We are shaping the world faster than we can change ourselves, and we are applying to the present the habits of the past." Was Churchill predicting the future of project management? Have we changed how we communicate and lead projects? Have leadership and management theories and models evolved to keep pace with today's business environment?Leading Virtual Project Teams: Adapting Leadership Theories and Communications Techniques to 21st Century Organizations addresses the challenges the virtual project management environment poses to traditional methods of leadership and communication. It introduces new approaches for adapting existing leadership theories to e-leadership as well as progressive tools and techniques to improve virtual project communications. The book begins by examining the factors affecting the movement from traditional work environments to virtual organizations. It considers the challenges of leading multicultural, global organizations and reviews what e-leadership means. Illustrating the application of both traditional and new leadership models and theories to virtual project management, the book includes best practices for:Managing and motivating the multicultural teamCommunicating in a distributed work environmentAvoiding social isolationCyber-bullying in the virtual environment and e-ethicsCultural management issues Explaining how traditional leadership theories and models can be applied to contemporary projects, the book details methods virtual project managers can use to enhance virtual communications. The final chapter describes the e-leadership skills and competencies project managers will need to ensure sustainable success in today's competitive business environment. This book provides the virtual project manager with the tools and techniques to improve e-leadership and communications. Complete with case studies that illustrate real-world applications to the virtual challenges presented in each chapter, the book is a suitable text for educational institutions looking to increase understanding of project management leadership and communications outside the traditional project environment.
Chapter 1. Overview -- Chapter 2. e-Leadership for projects -- Chapter 3. Enhancing virtual project communications -- Chapter 4. Cultural communication issues and effective e-leadership -- Chapter 5. Virtual project leadership competencies.
Includes bibliographical references and index.
Keywords: BUSINESS AND ECONOMICS